Chromosome Characterization of Brassicaceae Family - Ganies Riza Aristya; Bening Larasati; Galang Riswi Dyatama; Himawan Masyhuri; Febri Yuda Kurniawan; Fauzana Putri; Dian Astriana; Yuanita Rachmawati (Biotropic : The Journal of Tropical Biology, 2022)
Indonesia is known as a rich country in various agricultural and plantation products, including vegetables such as mustard, broccoli, cabbage, and cauliflower. However, in its cultivation, the products and demand for vegetables are not offset by an increase in the production quality. One of the efforts to improve and enhance the production quality is to identify and characterize chromosomes of plants which will become the basis for plant breeding activities. The purpose of this study was to characterize the number, form and size of the chromosome in cultivars belonging to the Brassicaceae family. The study was carried out using the modified squash method. Chromosomes were prepared by fixation, maceration, and staining, then the mitotic phases were observed using a microscope and optilab, and analyzed using Image Raster 3. The results showed that mitotic time range and chromosome character of six cultivars of the Brassicaceae family were different. Broccoli ('Chief No. 2 1955' and 'Green Super') and cauliflower ('ILONA' and 'TM 126') had a mitotic time range from 04.00 to 09.00 a.m. with 2n chromosome number = 18. Green mustard (‘Juwita’ and ‘TM Jade’) and white mustard ('Sakata' and 'Shuka-shuka') had a mitotic time range from 03.00 to 08.00 a.m. with 2n chromosome number = 20. White cabbage (‘CR ACE' and 'Sehati F1') had a mitotic time range from 04.00 to 09.00 a.m and red cabbage (‘Scarlet’ and ‘Red Globe’) had a mitotic time range from 09.00 to 10.00 a.m. with 2n chromosome number = 18.